SAT0335 SERUM AND BALF-DERIVED ANTI-JO1 AUTOANTIBODIES EXHIBIT HIGH REACTIVITY TO DISTINCT HISRS DOMAINS AND ASSOCIATE WITH LUNG AND JOINT INVOLVEMENT IN PATIENTS WITH IIM/ASS. (2nd June 2020) - Notarnicola, A.; Preger, C.; Lundström, S.; Renard, N.; Wigren, E.; Van Gompel, E.; Galindo-Feria, A. S.; Persson, H.; Fathi, M.; Grunewald, J.; Jakobsson, P. J.; Gräslund, S.; et al.
Abstract : Background: Autoantibodies that target aminoacyl transfer(t) RNA synthetases (aaRS) represent the serological marker of the anti-synthetase syndrome (ASS), a major subgroup of the idiopathic inflammatory myopathies (IIM) (1). Among the anti-aaRS, anti-histidyl tRNA synthetase (HisRS) autoantibodies (anti-Jo1) are the most common. Up to 90% of IIM/ASS patients diagnosed with interstitial lung disease (ILD) harbor anti-Jo1 autoantibodies (2). Objectives: Reactivity and affinity of anti-Jo1 autoantibodies from serum and broncheoalveolar lavage fluid (BALF) were investigated against HisRS autoantigen. Associations with clinical data from patients IIM/ASS were addressed. Methods: Total IgGs were purified by affinity chromatography. Samples and clinical data were obtained from: i) 26 anti-Jo1 + patients (19 at diagnosis, 16/19 at follow-up, 7 BALF/matching serum at baseline; ii) 29 anti-Jo1 - (25 serum at diagnosis, 4 BALF/matching serum at baseline); iii) 24 age/gender matched healthy controls. Anti-Jo1 IgG and IgA response against HisRS was evaluated by ELISA and western blot. Affinity was measured by surface plasmon resonance. HisRS full-length (HisRS-FL), two HisRS domains (ABD and CD), and two HisRS splice variants (WHEP and WHEP + ABD splice variant (SV)) were tested. Correlations between autoantibody reactivity and clinical data, at baseline and over disease course, were evaluated. Results: Anti-Jo1 autoantibodies from serum and lung bound HisRS-FL, WHEP and SV with high reactivity and affinity already at diagnosis and recognized both conformational and linear HisRS epitopes (Fig. 1). Levels of autoantibodies (against HisRS-FL, -domains and -splice variants) varied among patients and overtime. Patients with ILD, arthritis and less skin involvement presented higher anti-Jo1 titers compared to those with lower anti-Jo1 titers and to the anti-Jo1 negative group (Fig. 2). Anti-WHEP reactivity in BALF strongly correlated with poor pulmonary function. Conclusion: High reactivity and affinity at time of diagnosis indicates that autoimmunity against HisRS is most likely initiated before IIM/ASS diagnosis. Reactivity to specific splice variants of HisRS may be employed as diagnostic and prognostic markers. References: [1]Marguerie C, Bunn CC, Beynon HL, Bernstein RM, Hughes JM, So AK, Walport MJ: Polymyositis, pulmonary fibrosis and autoantibodies to aminoacyl-tRNA synthetase enzymes. Q J Med 1990, 77(282):1019-1038 [2]Richards TJ, Eggebeen A, Gibson K, Yousem S, Fuhrman C, Gochuico BR, Fertig N, Oddis CV, Kaminski N, Rosas IO et al: Characterization and peripheral blood biomarker assessment of anti-Jo-1 antibody-positive interstitial lung disease. Arthritis Rheum 2009, 60(7):2183-2192. Disclosure of Interests: Antonella Notarnicola: None declared, Charlotta Preger: None declared, Susanna Lundström: None declared, Nuria Renard: None declared, Edvard Wigren: None declared, Eveline Van Gompel: None declared, Angeles Shunashy Galindo-Feria: None declared, Helena Persson: None declared, Maryam Fathi: None declared, Johan Grunewald: None declared, Per-Johan Jakobsson Shareholder of: Gesynta Pharma, Grant/research support from: Gesynta Pharma, AstraZeneca, , Susanne Gräslund: None declared, Ingrid E. Lundberg Grant/research support from: Bristol Meyer Squibb, Corbus Pharmaceuticals, Inc and Astra Zeneca, Catia Cerqueira: None declared